PERLUASAN METODE INTEGRASI HASIL-KALI BERTIPE TRAPESIUM - Eko Budiansyah; Supriadi Putra; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the extension of the pro duct integration rules which is a modification of the generalized Euler-Maclaurin summation formula using a partition of the trap ezoidal metho d. Analytically, it is showed that this metho d has an error of O(1/n 2). Furthermore, computational results show that the method is superior to the comparison methods by looking into the error value obtained.